TEACHING VOCABULARY IN CONTEXTUALIZATION FOR YOUNG LEARNERS - Irwandi Irwandi; Gusti Milla Quaidy; Albert Albert (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
The primary focus of this study is to determine the effect of teaching vocabulary in contextualization for young learners. Vocabulary is one of the central components in a language included in English. According to Luppescu and Day (1993: 266)," Building a large vocabulary is essential when learning English because people with large vocabularies are more proficient than those with limited vocabularies. It occurs because the young learners who want to speak English with limited vocabulary, they will get difficulty during speaking with partners. They will stop their conversation or they will do code-mixing while talking with partners. It happens because the young learners will get the obstacle with the word that will be delivered because the speakers do not have enough storage in vocabulary. The obstacle appeared because the teachers order the young learners to memorize the word. Consequently, It can make the young learners easier to forget the words memorized by them. It happens because in that age (young learners), they need to understand the contex and the used of the each vocabularies that is provided by the teachers. Therefore, this study is proposed to solve the problem by giving the suggested strategy which is using contextualization in teaching vocabulary for young learners.